JUSTICE DIALOGUE IN THE PROCESS OF CRIMINAL JUSTICE - Teguh Ujang Bureni (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Criminal justice upholds law and justice based on material truth revealed in justice dialogue. Nowadays, the verdict of criminal justice does not reveal material truth. It is strongly presumed that there are some problems in justice dialogue. This normative juridical research with philosophical and conceptual approach describes the problems of justice dialogue in the process of criminal justice. Justice dialogue happened in the case of Blasphemy by Ahok and the case of Cocoa Stealing by Mina. The implementation of justice dialogue today is not in line with the principles of dialogue such as doubtful assumptions, freedom to have dialogue, imbalance chance of dialogue, sufficient attention, and best idea acceptance. Dialogue principles are violated in the case of blasphemy like sufficient attention and best idea acceptance. In the case of cacao stealing, the breaking of dialogue principles is doubtful assumptions, freedom to have dialogue, sufficient attention, and best idea acceptance. As a result, law and justice enforcement in criminal justice is not based on material truth. Keywords: Dialogue Principles, Justice Dialogue, Criminal Justice.